Stalagmite-like self-cleaning surfaces prepared by silanization of plasma-assisted metal-oxide nanostructures. Issue 9 (8th February 2016) - Yang, Ching-Yu; Chuang, Shang-I; Lo, Yu-Hsiang; Cheng, Hsin-Ming; Duh, Jenq-Gong; Chen, Po-Yu
Abstract : Robust stalagmite-like self-cleaning surfaces with good transparency and flexibility are developed by plasma-assisted nanofabrication and silanization under ambient conditions. Abstract : Effective self-cleaning coatings with liquid repellency are crucial for eliminating surface contamination and reducing drag force, which enables wide industrial applications. However, most coatings are fabricated through complicated and expensive processes that limit mass production capability. To overcome this limitation, we designed a simple methodology based on atmospheric-pressure-plasma-assisted fabrication. Hierarchically-structured, stalagmite-like tungsten oxide (WO3− x ) coatings were synthesized within a few seconds. After silanization, the coatings not only acquired cost-effective superhydrophobic surfaces with high static contact angles toward water (160° ± 2°, surface tension γ = 72.8 dyn cm −1 ), but showed oleophobicity toward liquids with lower surface tension, ranging from 64 to 27.5 dyn cm −1 . In addition, their two-tier topography decorated with fluoroalkylsilane traps air cushions within the textures, contributing to low sliding angle (<2°) and low contact angle hysteresis toward both water and glycerol. Their robust Cassie state can even sustain the high impact velocity of a liquid drop exceeding 2 m s −1 . Moreover, the coatings exhibited superior self-cleaning abilities and multi-functionality, including high transparency, flexibility, and mechanical and thermal stability. The growth mechanism of hierarchical WO3− x and the dynamic behavior of liquid droplets on the coatings were also investigated in this study. These micro- and nano-structures, which were constructed at room temperature enable seamless integration not only on brittle substrates but on various flexible substrates, such as plastic films and fibrous papers, without sacrificing performance.